Pengaruh pijat oksitosin terhadap peningkatan produksi ASI ibu postpartum - Juwariah, Juwariah; Fara, Yetty Dwi; Mayasari, Ade Tyas; Abdullah, Abdullah (Wellness And Healthy Magazine, 2020)
Breast milk is the best natural fluid that is needed by babies. Based on exclusive breast milk coverage in Indonesia on 2018 in the amount of 65,16 percent. The breast milk that came out a little will affect the breastfeeding process which will make exclusive breast milk unsuccessful. One effort that can be done to expedite breastfeeding in postpartum mothers is with oxytocin massage. The purpose of this research is to determine the effect of oxytocin message to the improvement of breastmilk production in postpartum mothers in PMB Langgeng Sri Asih on 2020. The type of this research uses a Quasi Experiment with the expansion of the non-equivalent control group pretest-posttest. The population of this research is postpartum mother 3-10 days in PMB Langgeng Sri Asih which amounted to 26 respondents. The sampling technique uses total sampling which is divided into 2 groups, namely 13 treatment group respondents and 13 control group respondents. This research is implemented on February 25 – March 25, 2020. The data analysis method uses a statistic analysis technique paired t-test and independent t-test. The result of this research obtained from 13 respondent carried out oxytocin message the average of milk production is 24,0 ml while 13 respondent did not do oxytocin message the average of milk production is 11,7 ml with significance (p = 0,001 less than 0,005), The conclusion of this study is that there is an effect of oxytocin massage on increasing milk production in postpartum mothers.